2013
DOI: 10.1186/1742-9994-10-17
|View full text |Cite
|
Sign up to set email alerts
|

‘Monster… -omics’: on segmentation, re-segmentation, and vertebrae formation in amphibians and other vertebrates

Abstract: BackgroundThe axial skeleton is one of the defining evolutionary landmarks of vertebrates. How this structure develops and how it has evolved in the different vertebrate lineages is, however, a matter of debate. Vertebrae and vertebral structures are derived from the embryonic somites, although the mechanisms of development are different between lineages.DiscussionUsing the anecdotal description of a teratological newt (Triturus dobrogicus) with an unusual malformation in its axial skeleton, we review, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…In all other amphibians that have been studied, the sclerotome is relatively small, which makes it difficult to observe the migration of sclerotome cells and to detect direct evidence for resegmentation (Wake, ; Wake and Lawson, ; Shishkin, ). Furthermore, formation of the vertebral column within amphibians appears to be a diverse process with variable patterns (Wake and Wake, ; Buckley et al, ) and even within salamanders, differences in the sclerotome (e.g., presence or absence of primary segmentation) have been observed that might affect vertebral column formation (Wake and Lawson, ; Buckley et al, ). If, and how, these differences affect the process of resegmentation is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all other amphibians that have been studied, the sclerotome is relatively small, which makes it difficult to observe the migration of sclerotome cells and to detect direct evidence for resegmentation (Wake, ; Wake and Lawson, ; Shishkin, ). Furthermore, formation of the vertebral column within amphibians appears to be a diverse process with variable patterns (Wake and Wake, ; Buckley et al, ) and even within salamanders, differences in the sclerotome (e.g., presence or absence of primary segmentation) have been observed that might affect vertebral column formation (Wake and Lawson, ; Buckley et al, ). If, and how, these differences affect the process of resegmentation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous morphological analysis based on histological sections yield indirect support for resegmentation in salamanders and frogs based on the observation that the vertebral centra develop in an intersegmental position (Mookerjee, 1930(Mookerjee, , 1931Wake, 1970;Wake and Lawson, 1973). However, whether resegmentation occurs in amphibians has remained an unsolved question, because the intersegmental position of a vertebra developing between two adjacent somites does not necessarily explain the migratory routes of sclerotomal cells from the somites, and it is possible that sclerotome cells from one somite form one vertebra without resegmentation (Wake, 1970;Verbout, 1976Verbout, , 1985Shishkin, 1989;Keller, 1999;Wake and Wake, 2000;Buckley et al, 2013). Furthermore, the scanty sclerotome in these groups of amphibians makes it more challenging to find conclusive evidence for or against resegmentation (Wake and Lawson, 1973;Wake and Wake, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of vertebrae in the fossil record and in modern embryology is not uncommon. The nature of fusion can be diverse, resulting from trauma, disease, or congenital malformation (Hanna, ; Buckeley et al ., ; Farke et al ., ; Xing et al ., ). While records of trauma and disease are well documented (Rothschild & Tanke, ; Molnar, ; Tanke & Rothschild, ; Rothschild, ), congenital vertebral pathologies are rarely reported from the fossil record.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital vertebral fusion can be classified as a defect of neural tube closure, a defect of formation, or a defect of segmentation (Kaplan et al, 2005). The presence of multiple fully formed neural spines, transverse processes, and ribs in NHCC LB337 suggests sclerotomal cell precursors were present and properly regionalized after somitogenesis and primary segmentation (Chandraraj, 1987;Buckeley et al, 2013). This, along with no apparent failure of midline fusion, suggests the neural tube closed normally at the level of these vertebrae.…”
Section: Nhcc Lb337mentioning
confidence: 99%
See 1 more Smart Citation